ANALISIS KEPRIBADIAN TOKOH BOK NAM DALAM FILM (BEDEVILLED): KAJIAN PSIKOANALISIS FREUD. - , NURFITRI SADJIDAH; , Yuni Wachid Asrori, S.S, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The paper entitled Bok Namâs Personality in ê¹ë³µë¨ì´ì¸ì¬ê±´ìì ë§ (Bedevilled): Freudâs Psychoanalysis Studies attempts to analyze the main character based on her personality. This movie was chosen as the object of this research because of its strong characterization through various dynamics happened to the personality of the main character. Moreover, this movie also depicts the way social conflicts influences, in this case drastically changes human personality. The personality of the main character was analyzed through descriptive theory by first describing the character and their characterization. Structuralism theory classified between the main character and the additional characters in the movie, and illustrated the characterizations of each character. The Freudâs Psychoanalysis approach was used. The approach from id, ego, and superego aspects was used to describe the personality of main character and the dynamics between the three aspects. The analysis of ê¹ë³µë¨ì´ì¸ì¬ê±´ìì ë§(Bedevilled) also describes the conflicts of main character with her best friend, her husband, her aunt, her daughter, and her internal conflicts with herself, and analyzes the main factor of those conflicts. The result of this graduating paper is that the social conflicts experienced by Bok Nam bring a very significant influence on Bok Namâs personality changes.